Risk-adjusted measures of value creation in financial institutions - Alistair Milne; Mario Onorato (Bank of Finland, 2009)
Measuring value creation by comparing the RAROC of an exposure (the return on risk capital) with a single institution-wide hurdle rate is inconsistent with the standard theory of financial valuation. We use asset pricing theory to determine the appropriate hurdle rate for such a RAROC performance measure. We find that this hurdle rate varies with the skewness of asset returns. Thus the RAROC hurdle rate should differ substantially between equity which has a right skew and debt which has a pronounced left skew and also between different qualities of debt exposure. We discuss implications for financial institution risk management and supervision.
URN:NBN:fi:bof-20140807570
Keywords: 330